2019
DOI: 10.1038/s41598-019-42053-9
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline orientation control of the platelet Nd2Fe14B phase to produce magnetic anisotropy via electromagnetic vibration processing

Abstract: Controlled crystalline orientation of the discontinuous phase in a composite enables the production of improved anisotropic properties, e.g., well-aligned Nd 2 Fe 14 B platelets by hot pressing and then soaking in a low-melting Nd-Cu eutectic melt to infiltrate to grain boundary. Alternatively, an anisotropic magnet can be fabricated by sintering Nd 2 Fe 14 B powder pre-aligned with a static magnetic field. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In addition to refining solidification structures, Tamura et al [34] found that the imposition of high-frequency EMV upon a bulk Mg 65 Cu 25 Y 10 alloy could improve the glass forming ability, which may be owing to the suppression of effective nucleation events at the frequency range. Very recently, the present authors [35] briefly reported that EMV could refine and align the Nd 2 Fe 14 B compound in Nd 70 Cu 30 -30 wt pct Nd 2 Fe 14 B alloys.…”
Section: Introductionmentioning
confidence: 71%
“…In addition to refining solidification structures, Tamura et al [34] found that the imposition of high-frequency EMV upon a bulk Mg 65 Cu 25 Y 10 alloy could improve the glass forming ability, which may be owing to the suppression of effective nucleation events at the frequency range. Very recently, the present authors [35] briefly reported that EMV could refine and align the Nd 2 Fe 14 B compound in Nd 70 Cu 30 -30 wt pct Nd 2 Fe 14 B alloys.…”
Section: Introductionmentioning
confidence: 71%